Structure/Function Studies and the Effects of Memantine in Monkeys with Experimental Glaucoma - Gabelt, B'Ann T. (The Association for Research in Vision and Ophthalmology, 2012)
PURPOSE. The scanning laser polarimetry with variable corneal compensation (GDx VCC) methodology was established and verified in monkeys with experimental glaucoma (ExpG). Terminal GDx parameters were correlated with axon counts and electrophysiologic measures. The effects of memantine on these parameters were investigated. METHODS. ExpG was induced in monkeys and intraocular pressure monitored weekly. Some monkeys received memantine in their diet before and after ExpG induction (1–10 months). GDx VCC scans, stereophotographs, and multifocal visual evoked potential (mfVEP) data were collected at baseline and every 6 to 8 weeks until euthanasia. Optic nerves were prepared for axon counting and other morphologic analysis. RESULTS. There was no difference in IOP elevation exposure between memantine-treated and no-memantine–treated monkeys. The percentage of the optic nerve area composed of connective tissue septa was significantly greater in ExpG eyes than in Fellow eyes. There was a strong positive correlation between axon counts and terminal GDx parameter measures. Animals not receiving memantine exhibited significantly lower mfVEP amplitudes in ExpG eyes compared with the ipsilateral baseline or the final value in the Fellow eye. ExpG eyes from memantine-treated animals had higher overall mean amplitudes that were not significantly different relative to the ipsilateral baseline and final amplitudes in the Fellow eye. CONCLUSIONS. The authors' studies confirm that GDx VCC can be utilized in monkey ExpG studies to detect early retinal structural changes and that these changes are highly correlated with optic nerve axon counts. These structural changes may or may not lead to central functional changes as shown by the mfVEP in response to investigational therapies.